PENGARUH PARTISIPASI ANGGARAN, KETEPATAN ANGGARAN TERHADAP SENJANGAN ANGGARAN DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL MODERASI (STUDI PADA PEMERINTAH KABUPATEN JAYAPURA) - Meise Kalembang; Paulus K. Allo Layuk; Syaikhul Falah (Universitas Cenderawasih, 2018)
The purpose of this research is to understand the influence of the participation and the budget acuracy against budget gap with a current commitment of organization as moderation variables. This kind of research is quantitative research by the use of the primary data. The research population is civil servants of SKPD in Jayapura regency. The amount of sample was 105. Method used in the study was moderated regression analysis. The results of this study found that the budgeting participation has a positive and significant impact on budget gap, while the budget accuracy can not have positive and significant impact on budget gap. Organization commitment as moderate variable cannot moderating budgeting participation and the budget accuracy to budget gap in Jayapura regency. Keywords: Budget participation, budget accuracy, budget gap, organization commitment.